2001
DOI: 10.1002/1616-3028(200110)11:5<374::aid-adfm374>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Open Circuit Voltage of Plastic Solar Cells

Abstract: A series of highly soluble fullerene derivatives with varying acceptor strengths (i.e., first reduction potentials) was synthesized and used as electron acceptors in plastic solar cells. These fullerene derivatives, methanofullerene [6,6]‐phenyl C61‐butyric acid methyl ester (PCBM), a new azafulleroid, and a ketolactam quasifullerene, show a variation of almost 200 mV in their first reduction potential. The open circuit voltage of the corresponding devices was found to correlate directly with the acceptor stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
1,219
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,764 publications
(1,309 citation statements)
references
References 19 publications
73
1,219
2
5
Order By: Relevance
“…In one study interface dipole layers of similar magnitude were found between the C 60 layer and the electrodes [32]. In another study it was shown that the open-circuit voltage of the PVDs was nearly independent of the metal workfunction and linearly proportional to the electron affinity of the C 60 derivative [33]. Although the interfaces were created under different experimental conditions, the results may properly be ascribed to an alignment of the LUMO of the C 60 -derivative to the Fermi level of the metal electrode.…”
Section: On Aumentioning
confidence: 81%
“…In one study interface dipole layers of similar magnitude were found between the C 60 layer and the electrodes [32]. In another study it was shown that the open-circuit voltage of the PVDs was nearly independent of the metal workfunction and linearly proportional to the electron affinity of the C 60 derivative [33]. Although the interfaces were created under different experimental conditions, the results may properly be ascribed to an alignment of the LUMO of the C 60 -derivative to the Fermi level of the metal electrode.…”
Section: On Aumentioning
confidence: 81%
“…These monomer units, especially in combination with electron-poor aromatic units, lead to novel polymeric electron donor structures [4][5][6][7][8] that possess a number of properties useful for increasing the photovoltaic response [2], such as an energy level alignment with electron acceptors [9]; a low energy gap which favours the light harvesting and increase the short-circuit current of the device [4]; a fair hole mobility [10] and good solubility in organic solvents and film forming characteristics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Typically in thin-film tandem cells, ultrathin doped layers are employed to form tunnel junctions between the sub-cells with extremely high doping 2,13,14 . Although ultrathin heavily n-doped a-Si:H film can be obtained, hole collection layer (HCL) for polymer cells such as MoO 3 sulfonate (PEDOT:PSS) can be neither ultrathin nor highly doped [20][21][22] . Therefore, we applied ZnO:Al or indium tin oxide (ITO) as interfacial conducting layers (ICLs) between a-Si:H and polymer cells, to promote electrical conduction.…”
Section: Resultsmentioning
confidence: 99%